2015
DOI: 10.3390/molecules200711808
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer, Antioxidant and Antimicrobial Properties of the Sesquiterpene β-Caryophyllene from the Essential Oil of Aquilaria crassna

Abstract: Abstract:The present study reports a bioassay-guided isolation of β-caryophyllene from the essential oil of Aquilaria crassna. The structure of β-caryophyllene was confirmed using FT-IR, NMR and MS. The antimicrobial effect of β-caryophyllene was examined using human pathogenic bacterial and fungal strains. Its anti-oxidant properties were evaluated by DPPH and FRAP scavenging assays. The cytotoxicity of β-caryophyllene was tested against seven human cancer cell lines. The corresponding selectivity index was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
391
1
15

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 655 publications
(431 citation statements)
references
References 38 publications
24
391
1
15
Order By: Relevance
“…Many studies have proven that extracts with antioxidant effects were also reported to have anticancer properties [29,[32][33][34][35]. This statement is in agreement with the current findings.…”
Section: Antioxidant Studies Of Passiflora Foetida Methanolic Extractsupporting
confidence: 93%
“…Many studies have proven that extracts with antioxidant effects were also reported to have anticancer properties [29,[32][33][34][35]. This statement is in agreement with the current findings.…”
Section: Antioxidant Studies Of Passiflora Foetida Methanolic Extractsupporting
confidence: 93%
“…Previous observation on the studies of Chinese toad Bufo gargarizans skin formulation (Chan Sue) was found to induce apoptosis in several human cancer cell lines such as (T24) human bladder carcinoma cells (Ko et al, 2005), (A549) human lung carcinoma (Yun et al, 2009). (HepG2) Hepatocarcinoma cells (Lu et al, 2011), (NHL) non-Hodgkin's lymphoma and (SP53) mantle cell lymphoma (Efuet et al, 2015). In order to obtain deeper insight into the apoptotic effect of TSS, the mitochondrial membrane potential was examined by staining the cells with lipophilic cationic dye rhodamine123 which can be easily absorbed by the mitochondria of live cells.…”
Section: Discussionmentioning
confidence: 97%
“…Detection of the changes in mitochondrial membrane potential in HCT 116 cells treated with TSS extract was assessed by the retention of Rhodamine 123 fluorescent dye following previous protocol (Dahham et al, 2015). Normally, the dye interacts with the inner mitochondrial negatively charged membrane and accumulates in normal mitochondria, but the reduction of mitochondrial membrane leads to the dye leakage which will result in reducing the fluorescence intensity.…”
Section: Detection Of Mitochondrial Membrane Potential Lossmentioning
confidence: 99%
“…α-Caryophyllene, known as humulene, is a naturally occurring monocyclic sesquiterpene. BCP, an isomer of α-caryophyllene, has been identified as an active component of an essential oil mixture that not only prevents solid tumor growth and proliferation of cancer cell lines but also inhibits lymph node metastasis of melanoma cells in high-fat diet-induced obese mice (78,79). Sarvmeili et al (80) reported that Pinus eldarica essential oil, of which BCP was the major component, exerts cytotoxic effects on HeLa and MCF-7 cell lines.…”
Section: Terpenes and Tumormentioning
confidence: 99%